2011
DOI: 10.1371/journal.pone.0018909
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Contributes to the Pathogenesis of Autoimmune Hepatitis through Inducing Hepatic Interleukin-6 Expression

Abstract: T helper cells that produce IL-17 (Th17 cells) have recently been identified as the third distinct subset of effector T cells. Emerging data suggests that Th17 cells play an important role in the pathogenesis of many liver diseases by regulating innate immunity, adaptive immunity, and autoimmunity. In this study, we examine the role and mechanism of Th17 cells in the pathogenesis of autoimmune hepatitis (AIH). The serum levels of IL-17 and IL-23, as well as the frequency of IL-17+ cells in the liver, were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
155
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 30 publications
9
155
0
9
Order By: Relevance
“…IL-17A production triggers several inflammatory conditions (26) and has been implicated in the establishment of liver fibrosis (42) and in the pathogenesis of alcoholic, autoimmune, and hepatitis B virus-or hepatitis C virus-related hepatitis (42)(43)(44)(45). Importantly, in all these chronic inflammatory conditions, IL-17-producing CD4 + T (Th17) cells were reported to be the major source of IL-17A in the liver, with few reports describing IL-17A-producing CD161 + CD8 + T cells (11,45).…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A production triggers several inflammatory conditions (26) and has been implicated in the establishment of liver fibrosis (42) and in the pathogenesis of alcoholic, autoimmune, and hepatitis B virus-or hepatitis C virus-related hepatitis (42)(43)(44)(45). Importantly, in all these chronic inflammatory conditions, IL-17-producing CD4 + T (Th17) cells were reported to be the major source of IL-17A in the liver, with few reports describing IL-17A-producing CD161 + CD8 + T cells (11,45).…”
Section: Discussionmentioning
confidence: 99%
“…The former are known to be important in the prevention of autoimmune diseases by maintaining immunological self-tolerance and experimental studies in the RRV murine model of BA have shown that lack of Tregs in the first three days of life allows an unopposed viral infection to cause bile duct inflammation and occlusion (16). Th-17 cells, by contrast, have a destructive role in autoimmune biliary diseases such as primary biliary cirrhosis (17) and autoimmune hepatitis (18).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have looked into the role of T H 17 cells in liver diseases; of these, there are reports of an elevated presence in patients with acute hepatic injury (Yasumi et al, 2007), in infection-induced hepatic granulomas (Heninger et al, 2006;Rutitzky et al, 2008), and in animal models of hepatic ischemia-reperfusion (Caldwell et al, 2005). A plethora of studies has investigated the association of circulating levels of IL-17 with individual liver diseases, including hepatitis B (Wang et al, 2011;Zhang et al, 2010), alcoholic hepatitis (Lemmers et al, 2009), autoimmune hepatitis (Zhao et al, 2011), and HCC (Wang et al, 2010;Zhang et al, 2009). Nevertheless, the role of T H 17 cells in the progression of HCV to cirrhosis and then to HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%